2012
DOI: 10.1042/cs20120021
|View full text |Cite
|
Sign up to set email alerts
|

The uroguanylin system and human disease

Abstract: The uroguanylin system is a newly discovered endocrine/paracrine system that may have a role in the regulation of salt balance, appetite and gut health. The precursor pro-uroguanylin is predominantly synthesized in the gut, although there may be other sites of synthesis, including the kidney tubules. Products from pro-uroguanylin may mediate natriuresis following oral consumption of a salt load through both GC-C (guanylate cyclase C)-dependent and -independent mechanisms, and recent evidence suggests a role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 81 publications
0
15
0
4
Order By: Relevance
“…In the intestinal tract, PKG-II is involved in the activation of the cystic fibrosis transmembrane regulator (CFTR) anion channel and chloride channels (ClC), causing the efflux of chloride and bicarbonate. Water is then effluxed into the intestinal lumen [47] . Upon binding of cGMP to the regulatory domain, the auto-inhibitory domain of PKG is released allowing binding of ATP in the catalytic domain and subsequent phosphorylation of target proteins.…”
Section: Interaction Of Pkg and The Wnt Signaling Cascadementioning
confidence: 99%
“…In the intestinal tract, PKG-II is involved in the activation of the cystic fibrosis transmembrane regulator (CFTR) anion channel and chloride channels (ClC), causing the efflux of chloride and bicarbonate. Water is then effluxed into the intestinal lumen [47] . Upon binding of cGMP to the regulatory domain, the auto-inhibitory domain of PKG is released allowing binding of ATP in the catalytic domain and subsequent phosphorylation of target proteins.…”
Section: Interaction Of Pkg and The Wnt Signaling Cascadementioning
confidence: 99%
“…In the intestine, GUCY2C-activated cGMP signaling regulates ion channels including the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel and CNG cation channels [4]. GUCY2C also inhibits sodium absorption from the intestinal lumen by sodium-hydrogen exchangers in brush border membranes [2, 4, 49]. In the brain, cGMP-dependent activation of CNG channels regulates neurotransmitter release and potentiates synaptic transmission through Ca 2+ influx [50, 51].…”
Section: Potential Molecular Mechanisms Underlying Gucy2c-mediated Samentioning
confidence: 99%
“…By decreasing AKT activation, GUCY2C signaling suppresses cell proliferation. Tellingly, the GUCY2C hormone guanylin is the most commonly lost gene product in sporadic colorectal cancer in mice and humans [49, 67]. GUCY2C silencing produces epithelial dysfunction, which is characterized by defective differentiation, an accelerated cell cycle, hyperproliferation, increased DNA damage, reprogramming of cell metabolism, and increased susceptibility to tumorigenesis induced by carcinogens or inherited germline mutations, resulting in increased intestinal tumorigenesis [5, 67].…”
Section: Obesity and Colorectal Cancermentioning
confidence: 99%
“…Beyond systemic volume homeostasis, GC-C/cGMP signal transduction mechanisms activated by GN and UGN regulate the formation of epithelial cells in the intestinal mucosa [98, 103]. Pitari et al [104] have shown that GN and UGN can regulate the balance between epithelial proliferation and differentiation, and can regulate cell cycle progression in human colon carcinoma cell lines.…”
Section: Non-classical Roles Of Guanylin Peptidesmentioning
confidence: 99%
“…GN and UGN exert a cytostatic effect on human colon carcinoma cells [109] and pancreatic cancer cells [110], and inhibit formation of cancerous intestinal polyps in mice [109]. Collectively, these data suggest that the UGN/GC-C/cGMP axis may have generalized antiproliferative properties in various organ systems [98, 103, 110, 111]. …”
Section: Non-classical Roles Of Guanylin Peptidesmentioning
confidence: 99%